2022
DOI: 10.1155/2022/6866000
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Effects of Electroacupuncture with Different Waveforms on Chronic Prostatitis/Chronic Pelvic Pain Syndromes: A Randomized Controlled Trial

Abstract: Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) is a common disorder in adult men. Evidence has demonstrated that acupuncture is effective for treating CP/CPPS. Electroacupuncture (EA) is a combination of traditional acupuncture and electrical stimulation, and the waveform is one of the key factors influencing EA effects. Different waveforms contain different stimulating parameters, thus generating different effects. However, the effects of different waveforms of EA on CP/CPPS remain unclear and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Based on traditional Chinese medical theory, Sanyinjiao and Sansili are acupuncture points commonly used for the treatment of CP/CPPS, which have the effects of benefiting Qi, regulating the meridians, regulating the bladder and draining Qi flow; additionally, Sansili tonifies Qi, infiltrates dampness, and induces diuresis. Therefore, electrical stimulation of the two acupoints can achieve the electroacupuncture effect, which improves immunity and effectively relieves symptoms such as prostatitis, erectile dysfunction, anxiety, and depression in patients with CP/CPPS[ 11 ]. Thus, the magnetic vibration magnetoelectric therapy instrument intervenes in patients with CP/CPPS through multiple pathways, promoting the absorption of local inflammatory substances in the prostate, relieving patient discomfort, and improving mood and quality of life by stimulating local tissue microcirculation and immune system function in the prostate.…”
Section: Discussionmentioning
confidence: 99%
“…Based on traditional Chinese medical theory, Sanyinjiao and Sansili are acupuncture points commonly used for the treatment of CP/CPPS, which have the effects of benefiting Qi, regulating the meridians, regulating the bladder and draining Qi flow; additionally, Sansili tonifies Qi, infiltrates dampness, and induces diuresis. Therefore, electrical stimulation of the two acupoints can achieve the electroacupuncture effect, which improves immunity and effectively relieves symptoms such as prostatitis, erectile dysfunction, anxiety, and depression in patients with CP/CPPS[ 11 ]. Thus, the magnetic vibration magnetoelectric therapy instrument intervenes in patients with CP/CPPS through multiple pathways, promoting the absorption of local inflammatory substances in the prostate, relieving patient discomfort, and improving mood and quality of life by stimulating local tissue microcirculation and immune system function in the prostate.…”
Section: Discussionmentioning
confidence: 99%
“…Electroacupuncture (EA) has been increasingly adopted for pain relief, and many clinical trials and animal experiments have demonstrated its analgesic effect [ 4 , 5 , 6 , 7 , 8 , 9 ]. It has been shown to induce the release of endogenous opioids, which desensitize peripheral nociceptors and inhibit inflammation [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%